Strained α-Sn thin films on highly lattice-mismatched Ge substrates - Tyler Stabile (Elsevier, 2021)
Strained α-Sn thin films and stanene (two-dimensional counterpart of α-Sn), which have attracted significant attentions due to their electronic properties as topological insulators, were mostly deposited on nearly lattice-matched substrates through molecular beam epitaxy. In this work, contrary to prior efforts, Sn thin films are deposited on highly lattice-mismatched Ge (100) substrates through physical vapor deposition of solid Sn sources. Three different methods, 1) Acetone/Isopropyl Alcohol (IPA), 2) Acetone/IPA/H2O(80°C), and 3) Hydrogen Peroxide (H2O2)/Hydrochloric Acid (HCl), are used to clean commercially available Ge (100) substrates. X-ray diffraction (XRD) characterizations indicate that compressively strained α-Sn thin films are formed on Ge substrates cleaned by Acetone/IPA/H2O(80°C) or H2O2/HCl, but no peak associated with crystalline α-Sn appears for thin films grown on Ge substrates cleaned by Acetone/IPA. Strained α-Sn thin films deposited on Ge substrates cleaned by Acetone/IPA/H2O(80°C) are further investigated using dielectric force microscopy (DFM). Although Ge substrates where α-Sn thin films are deposited are p-type, DFM images indicate that the α-Sn thin films are n-type. The α-Sn/Ge heterostructures that we demonstrate in this work might be promising in applications in advanced electronics and photonics.